Abnormal Contingent Negative Variation Drifts During Facial Expression Judgment in Schizophrenia Patients - Wang, Qian; She, Shenglin; Luo, Lu; Li, Haijing; Ning, Yuping; Ren, Jianjuan; Wu, Zhangying; Huang, Rongcheng; Zheng, Yingjun (Frontiers in Human Neuroscience, 2020)
Schizophrenia patients often show impaired facial expression recognition, which leads to difficulties in adaptation to daily life. However, it remains unclear whether the deficit is at the perceptual or higher cognitive level of facial emotion processing. Recent studies have shown that earlier face-evoked event-related potential components such as N170 and P100 can effectively distinguish schizophrenia patients from healthy controls; however, findings for later waveforms are ambiguous. To clarify this point, in this study we compared electroencephalographic signals in schizophrenia patients and control subjects during a facial expression judgment task. We found that group effects of the occipital N170 and frontal lobe contingent negative variation (CNV) were both significant. The effect sizes of N170 and CNV amplitudes were generally medium or small, whereas that of CNV slope for an upright face was large (> 0.8). Moreover, N170 amplitude and CNV slope but not CNV amplitude were correlated with Personal and Social Performance Scale score. These results suggest that the slope of CNV drift during facial expression processing has a potential clinical value for schizophrenia.